Water absorption by Brazil-Nut seeds - Reis, Geraldo Gonçalves dos (Pesquisa Agropecuaria Brasileira, 2014)
The water absorption was studied in Brazil-nut (Bertholletia excelsa, H.B.K) seeds of three and four striae, intact and with seedcoat weakened by scarification. In general, the seeds presented low water absorption in all treatments (< 26 percent of water absorption in relation to the initial weight). There was no difference in water absorption between three and four-striae seeds. Neither the exposure of the endosperm, the weakening of the seedcoat or the increase of the temperature were efficient to favor the water absorption by Brazil-nut seeds. This study confirms, in part, the hypothesis that the seedcoat does not impair the initial phase of water absorption in these seeds. It is possible, however, that the slow reactivation of the metabolism of these seeds, observed through the course of water absorption, are due, by and large, to seedcoat and/or endosperm impermeability to gaseous exchange, and/or to the presence of germination inhibitors, and/or to a poor morphophysiologic development of the embryo.